Documento curricular do município de Abaetetuba: a sustentabilidade e a formação da consciência ambiental presente no componente curricular história - SANTOS, Henrique Darlen Tavares dos (2022)
The present work is a documental study about the Curricular Document of the Municipality of Abaetetuba/DCMA, discussing sustainability and the formation of the environmental conscience present in the history curriculum component. The objective is to reflect on the notion of sustainability present in the curriculum component History of the Curriculum Document of the Municipality of Abaetetuba/DCMA and analyze whether the selected knowledge contributes to the formation of environmental awareness in elementary school. As a theoretical guideline for the construction of this work, authors who deal with themes adjacent to what was explained were used, such as Reigota (1998), Carvalho (2001), Pacheco (2001), Santos (2009). As a result, we were able to identify and infer that: 1 - the content on the sustainability of the DCMA History curriculum component for elementary education is limited because there is only one content to be worked on from the 1st to the 5th year, 2 - this content on sustainability does not seem to be enough for real awareness of the environment, 3 - the training project needs to focus on school experiences that involve school knowledge, aiming at sustainability and environmental awareness, to protect society and the environment.